Karakteristik Tanah Ultisol Pasca Pemberian Pupuk Kascing dan Pertumbuhan Bibit Kakao - Ida Nursanti (JURNAL AGRI-TEK : Jurnal Penelitian Ilmu-Ilmu Eksakta, 2023)
Abstract--Ultisol soil has low organic matter content, high levels of leaching and evaporation, high Al saturation, and low nutrient availability. To overcome several ultisol soil problems, it is necessary to apply vermicompost fertilizer. Vermicompost is compost from soil used to raise worms, which affects soil structure and contains N, P, K, CA, Mg, S, and Fe. The research aimed to determine the characteristics of ultisol soil after applying vermicompost fertilizer and the growth of cocoa seedlings. Implementation of Research at the Pijoan Experimental Garden, Batanghari Regency. The experiment used a Completely Randomized Design (CRD). Observation data were analyzed using analysis of variance and the Duncan New Multiple Range Test (DNMRT) at the 5% level. The treatment tried was vermisol fertilizer with four dose levels, K0: 100% ultisol soil, K1: 85% ultisol soil + 15% vermisol fertilizer, K2: 75% ultisol soil + 25% vermisol fertilizer, K3: 65% ultisol soil + 35 % vermicompost per polybag. Providing vermicompost fertilizer with K2 and K3 treatment can increase N-total, P-Bray 1, and C-organic soil, increasing the pH of ultisol soil. Fertilizing vermicompost on ultisol soil had a significant effect on shoot dry weight and cocoa plant quality index. However, it had no significant effect on plant height, stem diameter and root dry weight.